Positive electrode material and preparation method and application thereof
Through multiple sintering and cation exchange resin coating technology, a stable metal oxide coating layer is formed, which solves the problems of structural instability and poor interface stability of medium nickel ternary positive electrode materials under high voltage, and improves cycling performance and surface Stability, suitable for high voltage lithium-ion batteries.
Patent Information
- Application Number
- CN202310795554.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
The structure of the medium nickel ternary positive electrode material is prone to collapse under high voltage, has increased impedance, cyclic attenuation, and poor surface crystal structure stability, resulting in the problems of short battery cycle life and low thermal stability.
Multiple sintering and surface modification methods are used to form a uniform metal oxide coating on the surface of the positive electrode material through the adsorption of the cation exchange resin, block the side reaction between the electrolyte and the positive electrode material, enhance the surface stability, and use gradient doping. Avoid capacity loss caused by multi-element doping.
It significantly improves the cycling performance and surface stability of the positive electrode material at high voltage, avoids capacity loss caused by multi-element doping, and is suitable for high voltage systems above 4.4V.
Smart Images

Figure CN119219072A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a positive electrode material and a preparation method and application thereof. Background Art
[0002] With the continuous development of the new energy industry, people have increasingly stringent requirements on the energy density and safety performance of lithium-ion power batteries. At the same time, with the soaring prices of lithium battery raw materials, it is necessary to reduce costs and increase efficiency to innovate the lithium battery material system. Focusing on ternary positive electrode materials, high nickel, high voltage and single crystal have become trends. At present, high voltage is based on medium nickel ternary materials, which are superior to high nickel ternary in terms of raw materials, production process, processing cost and safety performance; for medium nickel materials, there are mainly two morphologies: agglomerates and single crystals. Agglomerates are secondary balls composed of tiny primary particles. Secondary balls are easily broken during high voltage charging and discharging, resulting in aggravated side reactions and poor thermal stability. Single crystal ternary materials have the characteristics of good particle single crystalization and high mechanical strength. They will not cause particle breakage during charging and discharging, and can effectively reduce side reactions at the interface between materials and electrolytes. They can not only improve the capacity of medium nickel ternary materials under high voltage, but also effectively improve the poor high temperature cycle and fast capacity decay of materials.
[0003] However, the current high-voltage medium-nickel ternary cathode materials are still facing a series of challenges. For example, under high voltage, due to the large amount of lithium ion release, a series of problems such as easy structural collapse, increased impedance, cycle attenuation, poor surface crystal structure stability, and serious interface side reactions, resulting in macroscopic battery failure behaviors such as short battery cycle life and low thermal stability. In order to improve the cycle performance of medium-nickel single crystal materials under high voltage, secondary sintering is generally used, multi-element doping is performed in the first sintering, and the secondary sintering is used for coating and multi-element doping. The electrochemical performance of the ternary cathode material is improved through the synergistic effect of the composite doping elements.
[0004] CN 115911300A discloses a method for preparing a high-voltage ternary positive electrode material, comprising the following steps: step 1: uniformly mixing a lithium salt, a ternary precursor containing nickel, cobalt and manganese, and a dopant, and then sintering once to obtain a primary sintered material; step 2: crushing the primary sintered material, mixing and coating the material with a coating agent A, and then sintering twice to obtain a primary coated material having a first coating layer; the coating agent A is one or more combinations of corresponding element compounds of Li, Al, Ti, Mg, Co, Sr, Ba, B, Na, Sn, P, F, and Sm; step 3: crushing the primary coated material, mixing and coating it with a coating agent B, and then sintering three times to obtain a ternary positive electrode material having a second coating layer; the coating agent B is one or more combinations of corresponding element compounds of Ti, Al, B, Ti, Zr, W, Y, P, F, Li, and B.
[0005] However, doping with multiple elements will lead to a decrease in material capacity and reduce the energy density of the ternary positive electrode material. Surface coating can play a certain protective role on the material surface and inhibit the corrosion of the electrolyte on the positive electrode material. But overall, the medium nickel single crystal material still cannot show good cycle performance under high voltage.
[0006] Based on the above research, it is necessary to provide a method for preparing a positive electrode material, which can improve the bulk structure stability, surface crystal structure stability and surface stability of the material as a whole through coordination between steps, so that the material has excellent capacity and cycle performance under high voltage. Summary of the invention
[0007] The object of the present invention is to provide a positive electrode material and a preparation method and application thereof. The preparation method enhances the surface crystal structure stability of the material through multiple sintering and surface modification, binds metal cations to the surface of the positive electrode material, and obtains a uniformly coated positive electrode material after roasting, which effectively blocks the side reaction between the electrolyte and the positive electrode material, reduces the side reaction between the material surface and the electrolyte, greatly enhances the surface stability of the material, solves the problem of structural instability and poor interface stability of the material under high voltage, significantly improves the cycle performance of the material, and does not cause the capacity loss problem caused by multi-element doping. The material can be applied in high voltage systems above 4.4V.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a positive electrode material, the preparation method comprising the following steps:
[0010] (1) mixing a precursor and a lithium source and sintering them once to obtain a sintered product;
[0011] (2) sintering the first sintered product in step (1) for a second time to obtain a second sintered product;
[0012] (3) Mixing the cation exchange resin, the metal salt and the second sintered product of step (2), and then sintering for three times to obtain the positive electrode material.
[0013] On the one hand, the present invention uses multiple sintering to make the prepared material have a high degree of single crystallization and good roundness. At the same time, particles that have not formed good single crystals in the first powder can grow further, especially the secondary sintering process, which not only repairs the morphology of the material, but also can be sintered in an air atmosphere; on the other hand, the present invention does not use a conventional coating method, but uses the adsorption effect of a cation exchange resin to simultaneously coat the cation exchange resin and cations on the second sintered product, and then sintering for three times to obtain a uniform metal compound coating layer. At the same time, since the cation exchange resin is cracked and carbonized after sintering, the coating layer can also include residual carbon, and a uniform coating layer including carbon and metal oxides is obtained, which effectively blocks the side reaction between the electrolyte and the positive electrode material, reduces the side reaction between the material surface and the electrolyte, and greatly enhances the surface stability of the material. At the same time, since the coating layer contains carbon, the electrical conductivity of the material is also improved.
[0014] Preferably, the cation exchange resin in step (3) comprises a gel-type cation exchange resin.
[0015] Since ion exchange resin is a solid macromolecule, it is difficult to coat and compound with the positive electrode material. Therefore, the present invention adopts a gel-type cation exchange resin, so that the surface of the positive electrode material can be evenly coated with a layer of gel resin, and the cation exchange resin can further adsorb cations, so that the cation exchange resin and its ability to adsorb metal cations can be combined with the coating of the positive electrode material.
[0016] Preferably, the gel-type cation exchange resin comprises polymethyl methacrylate-ethylene glycol dimethacrylate copolymer.
[0017] The main component of the gel-type cation exchange resin of the present invention is a polymer, which is prepared by free radical polymerization reaction with methyl methacrylate (MMA) and ethylene glycol dimethacrylate (EDMA) as main raw materials. During the polymerization process, cationic monomers such as acrylic acid, methacrylic acid, 4-sulfonic acid styrene, etc. are added to make the resin surface have positive charges.
[0018] Preferably, a solvent is also added during the mixing process in step (3).
[0019] Preferably, the solvent comprises water.
[0020] Preferably, the mixing in step (3) comprises first mixing the cation exchange resin and the solvent, and then adding the metal salt and the di-sintered product in step (2) for mixing.
[0021] Preferably, in the mixture obtained by mixing the cation exchange resin and the solvent, the content of the cation exchange resin is 0.05-0.2wt%, for example, it can be 0.05wt%, 0.1wt%, 0.15wt% or 0.2wt%, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] Since the present invention adopts a gel-type cation exchange resin, in order to avoid the problem that the gel-type cation exchange resin cannot be effectively coated, the gel-type cation exchange resin of the present invention needs to be mixed with a solvent to prepare a mixture with a specific content. If the content of the cation exchange resin is too low or too high, it cannot be effectively and evenly coated.
[0023] Preferably, in the mixture obtained by mixing in step (3), the concentration of the metal salt is 0.05-2.5 mol / L, for example, it can be 0.05 mol / L, 0.1 mol / L, 1 mol / L, 1.5 mol / L or 2.5 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the metal salt in step (3) comprises any one of aluminum salt, cobalt salt or niobium salt, or a combination of at least two of them.
[0025] Preferably, the temperature of the three sinterings in step (3) is 400-650°C, for example, 400°C, 500°C, 600°C or 650°C, the time is 7-12h, for example, 7h, 9h, 11h or 12h, and the heating rate is 2-8°C / min, for example, 2°C / min, 4°C / min, 6°C / min or 8°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the three sintering steps in step (3) are carried out in an air atmosphere.
[0027] Preferably, after the mixing in step (3) and before the three sinterings, the solvent is first removed, and the method of removing the solvent includes drying and / or rotary evaporation, preferably rotary evaporation.
[0028] In order to ensure the uniformity of coating, the present invention takes into account the gel of the cation exchange resin. After the cation exchange resin, the metal salt and the second calcined product of step (2) are mixed, the solvent is directly removed by drying and / or rotary evaporation to ensure effective coating of the gel-type cation exchange resin.
[0029] Preferably, after the three sinterings, screening and iron removal are carried out in sequence.
[0030] Preferably, before the secondary sintering in step (2), the first sintered product is first mixed with an additive.
[0031] Preferably, the additive includes an M-containing dopant and / or a P-containing dopant, wherein M includes any one of Al, Zr or Co or a combination of at least two thereof, and P includes any one of Sr, Y or Ti or a combination of at least two thereof.
[0032] Preferably, in step (2), the mass ratio of the sintered product to the dopant containing M is 1:(0.0001-0.1), for example, it can be 1:0.0001, 1:0.001, 1:0.01 or 1:0.1, and the mass ratio of the sintered product to the dopant containing P is 1:(0.0001-0.1), for example, it can be 1:0.0001, 1:0.001, 1:0.01 or 1:0.1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the temperature of the secondary sintering in step (2) is 600-850°C, for example, 600°C, 700°C, 800°C or 850°C, the time is 5-12h, for example, 5h, 8h, 10h or 12h, and the heating rate is 2-8°C / min, for example, 2°C / min, 4°C / min, 6°C / min or 8°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the atmosphere for the secondary sintering in step (2) is an air atmosphere.
[0035] Preferably, after the secondary sintering in step (2), the sintered material is crushed to obtain a second sintered product, wherein the crushing method includes any one of jaw crushing, roller crushing, mechanical crushing or air flow crushing, or a combination of at least two of them.
[0036] Preferably, a first dopant and a second dopant are also added during the mixing process in step (1).
[0037] Preferably, the mass ratio of the precursor to the first dopant is 1:(0.0001-0.1), for example, it can be 1:0.0001, 1:0.001, 1:0.01 or 1:0.1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the mass ratio of the precursor to the second dopant is 1:(0.0001-0.1), for example, it can be 1:0.0001, 1:0.001, 1:0.01 or 1:0.1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] Preferably, the first dopant is an M-containing dopant, and the second dopant is an N-containing dopant, wherein M includes any one of Al cations, Zr cations or Co cations or a combination of at least two thereof, and N includes any one of Mg cations, Ce cations, Sr cations, Y cations, W cations, Mo cations or Nb cations or a combination of at least two thereof.
[0040] The present invention firstly dopes part of the M-containing dopant in a primary sintering process, and then dopes the remaining M-containing dopant in a secondary sintering process. By adding a sintering step, part of the element M originally doped in the primary sintering is doped in the secondary sintering, and the gradient distribution of the element M is achieved by controlling the temperature of the secondary sintering, thereby solving the problem of capacity loss caused by multi-element doping. At the same time, it can avoid the transformation of the layered structure into the spinel phase and the rock salt phase during the high voltage cycle process, thereby enhancing the surface crystal structure stability of the material. At the same time, the secondary sintering also repairs the material morphology and improves the single crystal degree of the material.
[0041] Preferably, the primary sintering temperature in step (1) is 800-980°C, for example, 800°C, 850°C, 900°C, 950°C or 980°C, the time is 6-17h, for example, 6h, 10h, 15h or 17h, the heating rate is 2-8°C / min, for example, 2°C / min, 4°C / min, 6°C / min or 8°C / min, and the atmosphere is an oxygen atmosphere.
[0042] Preferably, after the primary sintering in step (1), the sintered material is crushed to obtain a sintered product, wherein the crushing method includes any one of jaw crushing, roller crushing, mechanical crushing or air flow crushing, or a combination of at least two of them.
[0043] Preferably, the precursor in step (1) is Ni x Co y Mn z (OH)2, wherein 0.6≤x≤0.7, for example, 0.6, 0.65 or 0.7, 0.05≤y≤0.2, for example, 0.05, 0.1 or 0.2, 0.2≤z≤0.3, for example, 0.2, 0.25 or 0.3, and x+y+z=1.
[0044] Preferably, the particle size D50 of the precursor in step (1) is 3-5 μm, for example, 3 μm, 4 μm or 5 μm, and BET ≥ 8 μm 2 / g, for example, it can be 8m 2 / g, 10m 2 / g, 12m 2 / g or 14m 2 / g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] Preferably, the lithium source in step (1) comprises any one of lithium carbonate, lithium hydroxide or lithium acetate, or a combination of at least two of them.
[0046] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0047] (1) mixing a precursor, a lithium source, a first dopant, and a second dopant, and then sintering them in an oxygen atmosphere at a temperature of 800-980° C. for 6-17 h at a heating rate of 2-8° C. / min, and then pulverizing to obtain a sintered product;
[0048] Wherein, the mass ratio of the precursor to the first dopant is 1:(0.0001-0.1), and the mass ratio of the precursor to the second dopant is 1:(0.0001-0.1);
[0049] (2) mixing the additive with the first sintered product of step (1), and then sintering the second sintered product at a temperature of 600-850° C. for 5-12 h in an air atmosphere at a heating rate of 2-8° C. / min, and then pulverizing the second sintered product.
[0050] (3) mixing a cation exchange resin and a solvent to obtain a mixture having a cation exchange resin content of 0.05-0.2 wt %, adding a metal salt and the second calcined product of step (2) to the mixture to obtain a mixture having a metal salt concentration of 0.05-2.5 mol / L, drying and / or rotary evaporation to remove the solvent, and sintering the mixture three times at a temperature of 400-650° C. for 7-12 h at a heating rate of 2-8° C. / min in an air atmosphere to obtain the positive electrode material;
[0051] Wherein, the cation exchange resin is a gel-type cation exchange resin.
[0052] In a second aspect, the present invention provides a positive electrode material, which is prepared by the preparation method described in the first aspect.
[0053] In a third aspect, the present invention provides a battery, comprising the positive electrode material as described in the second aspect.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] (1) The present invention solves the problems of unstable structure and poor interface stability of positive electrode materials under high voltage, significantly improves the cycle performance of the material, and does not cause the capacity loss problem caused by multi-element doping, so that the obtained positive electrode material can be used in high voltage systems above 4.4V;
[0056] (2) The present invention adds cation exchange resin, and through its exchange effect, metal ions are attached to its surface, and the adsorption effect of the cation exchange resin is used to bind the resin and its cations to the surface of the positive electrode material. After three sinterings, a positive electrode material with a uniform coating layer is obtained, which effectively blocks the side reaction between the electrolyte and the positive electrode material, reduces the side reaction between the material surface and the electrolyte, and greatly enhances the surface stability of the material;
[0057] (3) The present invention avoids the capacity loss caused by multi-element doping by doping part of the element M originally doped in the first sintering in the second sintering, and then realizes the gradient doping of the element M on the surface of the material by controlling the temperature of the second sintering, thereby avoiding the transformation of the layered structure into the spinel phase and the rock salt phase during the high voltage cycle, enhancing the surface crystal structure stability of the material, and at the same time, the gradient of the single crystal material also improves the capacity of the material;
[0058] (4) The present invention prepares the positive electrode material by three sintering steps, wherein the second sintering process repairs the morphology of the material, so that the prepared material has a high degree of single crystallinity and good roundness. At the same time, particles in the powder that have not formed good single crystals can grow further. At the same time, during the second sintering, an air atmosphere can be used to reduce the processing cost of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is a morphology diagram of a fired product according to Example 1 of the present invention;
[0060] Figure 2 This is a morphology diagram of the second fired product described in Example 1 of the present invention;
[0061] Figure 3 This is a morphology diagram of the positive electrode material described in Example 1 of the present invention;
[0062] Figure 4 This is a morphology diagram of a fired product according to Example 2 of the present invention;
[0063] Figure 5 This is a morphology diagram of the second fired product described in Example 2 of the present invention;
[0064] Figure 6 This is a morphology diagram of the positive electrode material described in Example 2 of the present invention. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] Example 1
[0067] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:
[0068] (1) mixing a precursor, a lithium source, a first dopant and a second dopant, and then sintering the mixture in an oxygen atmosphere at a temperature of 938° C. for 11 h at a heating rate of 5° C. / min, and then crushing the mixture by a jaw crusher and a double roller mill, and then crushing and classifying the crushed material by a jet mill to obtain a sintered product;
[0069] The precursor has a particle size of D50 of 3 μm and a BET of 10 μm. 2 / gNi 0.65 Co 0.07 Mn 0.28 (OH)2, the lithium source is lithium carbonate, the first dopant is CoOOH, the second dopant is Y2O3 and SrCO3 in a mass ratio of 0.2:0.15, the mass ratio of the precursor to the first dopant is 1:0.002, and the mass ratio of the precursor to the second dopant is 1:0.0035;
[0070] (2) mixing the additive with the first sintered product of step (1), and then sintering the product for a second time at 750° C. for 8 h in an air atmosphere at a heating rate of 5° C. / min, and then crushing the product by jaw crushing, double roller mill crushing and air flow milling to obtain a second sintered product;
[0071] Wherein, the additive is CoOOH, and the mass ratio of the sintered product to the additive is 1:0.002;
[0072] (3) mixing a cation exchange resin and a solvent to obtain a mixture having a cation exchange resin content of 0.1 wt %, adding a metal salt and the second calcined product of step (2) to the mixture to obtain a mixture having a metal salt concentration of 1 mol / L, then performing rotary evaporation to remove the solvent, and then sintering three times at a temperature of 450° C. for 8 h in an air atmosphere at a heating rate of 5° C. / min, and finally sieving and removing iron to obtain the positive electrode material;
[0073] Wherein, the cation exchange resin is a gel-type cation exchange resin, the gel-type cation exchange resin includes polymethyl methacrylate-ethylene glycol dimethacrylate copolymer, the solvent is water, and the metal salt is aluminum nitrate;
[0074] The morphology of a fired product described in this embodiment is as follows Figure 1As shown, the morphology of the second fired product is as follows Figure 2 As shown in the figure, the morphology of the positive electrode material is as follows Figure 3 shown.
[0075] Example 2
[0076] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:
[0077] (1) mixing a precursor, a lithium source, a first dopant and a second dopant, and then sintering the mixture in an oxygen atmosphere at a temperature of 945° C. for 10 h at a heating rate of 5° C. / min, and then crushing the mixture by a jaw crusher and a double roller mill, and then crushing and classifying the crushed material by a jet mill to obtain a sintered product;
[0078] The precursor has a particle size of D50 of 3.5 μm and a BET of 10 μm. 2 / gNi 0.6 Co 0.1 Mn 0.3 (OH)2, the lithium source is lithium carbonate, the first dopant is CoOOH, the second dopant is Y2O3 and ZrO2 in a mass ratio of 0.15:0.2, the mass ratio of the precursor to the first dopant is 1:0.001, and the mass ratio of the precursor to the second dopant is 1:0.0035;
[0079] (2) mixing the additive with the first sintered product of step (1), and then sintering the product for a second time at 730° C. for 8 h at a heating rate of 5° C. / min in an air atmosphere, and then crushing the product by jaw crushing, double roller mill crushing and air flow milling to obtain a second sintered product;
[0080] The additives are Al2O3 and CoOOH in a mass ratio of 0.2:0.6, and the mass ratio of the sintered product to the additive is 1:0.008;
[0081] (3) mixing a cation exchange resin and a solvent to obtain a mixture having a cation exchange resin content of 0.1 wt %, adding a metal salt and the second calcined product of step (2) to the mixture to obtain a mixture having a metal salt concentration of 1 mol / L, then performing rotary evaporation to remove the solvent, and then sintering three times at a temperature of 450° C. for 8 h in an air atmosphere at a heating rate of 5° C. / min, and finally sieving and removing iron to obtain the positive electrode material;
[0082] Wherein, the cation exchange resin is a gel-type cation exchange resin, the gel-type cation exchange resin includes polymethyl methacrylate-ethylene glycol dimethacrylate copolymer, the solvent is water, and the metal salt is Al(NO3)3;
[0083] The morphology of a fired product described in this embodiment is as follows Figure 4 As shown, the morphology of the second fired product is as follows Figure 5 As shown in the figure, the morphology of the positive electrode material is as follows Figure 6 shown.
[0084] Example 3
[0085] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:
[0086] (1) mixing a precursor, a lithium source, a first dopant, and a second dopant, and then sintering them at 800° C. for 17 h in an oxygen atmosphere at a heating rate of 2° C. / min, and then air flow pulverizing to obtain a sintered product;
[0087] The precursor has a particle size of D50 of 5 μm and a BET of 8 μm. 2 / gNi 0.65 Co 0.07 Mn 0.28 (OH)2, the lithium source is lithium carbonate, the first dopant is CoOOH, the second dopant is Y2O3 and SrCO3 in a mass ratio of 0.2:0.15, the mass ratio of the precursor to the first dopant is 1:0.0001, and the mass ratio of the precursor to the second dopant is 1:0.1;
[0088] (2) mixing the additive with the first sintered product of step (1), and then sintering the product for a second time at 850° C. for 5 h at a heating rate of 8° C. / min in an air atmosphere, and then crushing the product by jaw crushing, double roller mill crushing and air flow milling to obtain a second sintered product;
[0089] Wherein, the additive is CoOOH, and the mass ratio of the sintered product to the additive is 1:0.1;
[0090] (3) mixing a cation exchange resin and a solvent to obtain a mixture having a cation exchange resin content of 0.2 wt %, adding a metal salt and the second calcined product of step (2) to the mixture to obtain a mixture having a metal salt concentration of 0.05 mol / L, drying to remove the solvent, sintering the mixture three times at a temperature of 650° C. for 7 h at a heating rate of 8° C. / min in an air atmosphere, and finally sieving and removing iron to obtain the positive electrode material;
[0091] Wherein, the cation exchange resin is a gel-type cation exchange resin, which includes polymethyl methacrylate-ethylene glycol dimethacrylate copolymer, the solvent is water, and the metal salt is aluminum nitrate.
[0092] Example 4
[0093] This embodiment provides a method for preparing a positive electrode material, the preparation method comprising the following steps:
[0094] (1) mixing a precursor, a lithium source, a first dopant, and a second dopant, and then sintering them at a temperature of 980° C. for 6 h at a heating rate of 8° C. / min in an oxygen atmosphere, and then air flow pulverizing them to obtain a sintered product;
[0095] The precursor has a particle size of D50 of 0.1 μm and a BET of 8 μm. 2 / gNi 0.65 Co 0.07 Mn 0.28 (OH)2, the lithium source is lithium carbonate, the first dopant is CoOOH, the second dopant is Y2O3 and SrCO3 in a mass ratio of 0.2:0.15, the mass ratio of the precursor to the first dopant is 1:0.1, and the mass ratio of the precursor to the second dopant is 1:0.0001;
[0096] (2) mixing the additive with the first sintered product of step (1), and then sintering the product for a second time at 600° C. for 12 h in an air atmosphere at a heating rate of 2° C. / min, and then crushing the product by jaw crushing, double roller mill crushing and air flow milling to obtain a second sintered product;
[0097] Wherein, the additive is CoOOH, and the mass ratio of the sintered product to the additive is 1:0.0001;
[0098] (3) mixing a cation exchange resin and a solvent to obtain a mixture having a cation exchange resin content of 0.05 wt %, adding a metal salt and the second calcined product of step (2) to the mixture to obtain a mixture having a metal salt concentration of 2.5 mol / L, drying to remove the solvent, sintering the mixture three times at a temperature of 400° C. for 12 h at a heating rate of 2° C. / min in an air atmosphere, and finally sieving and removing iron to obtain the positive electrode material;
[0099] Wherein, the cation exchange resin is a gel-type cation exchange resin, which includes polymethyl methacrylate-ethylene glycol dimethacrylate copolymer, the solvent is water, and the metal salt is aluminum nitrate.
[0100] Example 5
[0101] This embodiment provides a method for preparing a positive electrode material. The preparation method is the same as that of Embodiment 1 except that the polymethyl methacrylate-ethylene glycol dimethacrylate copolymer in step (3) is replaced by Nafion perfluorosulfonic acid resin.
[0102] Example 6
[0103] This embodiment provides a method for preparing a positive electrode material. The preparation method is the same as that of Embodiment 1 except that the polymethyl methacrylate-ethylene glycol dimethacrylate copolymer in step (3) is replaced by polystyrene sulfonic acid resin.
[0104] Example 7
[0105] This embodiment provides a method for preparing a positive electrode material. The preparation method is the same as that of Embodiment 1 except that the content of the cation exchange resin in step (3) is 0.01 wt %.
[0106] Example 8
[0107] This embodiment provides a method for preparing a positive electrode material. The preparation method is the same as that of Embodiment 1 except that the content of the cation exchange resin in step (3) is 0.4 wt %.
[0108] Example 9
[0109] This embodiment provides a method for preparing a positive electrode material. The preparation method is the same as that of Embodiment 1 except that no solvent is added during mixing in step (3), and the cation exchange resin, the metal salt and the second calcined product of step (2) are directly mixed.
[0110] Example 10
[0111] This embodiment provides a method for preparing a positive electrode material. The preparation method is the same as that of Embodiment 1 except that the additive in step (2) is added together with the first dopant in step (1).
[0112] Embodiment 11
[0113] This embodiment provides a method for preparing a positive electrode material. The preparation method is the same as that of Embodiment 1 except that in step (1), the first dopant is added together with the additive in step (2).
[0114] Comparative Example 1
[0115] This comparative example provides a method for preparing a positive electrode material. The preparation method is the same as Example 1 except that step (2) is not performed.
[0116] Comparative Example 2
[0117] This comparative example provides a method for preparing a positive electrode material. The preparation method is the same as Example 1 except that step (3) is not performed.
[0118] Comparative Example 3
[0119] This comparative example provides a method for preparing a positive electrode material. The preparation method is the same as Example 1 except that no cation exchange resin is added in step (3).
[0120] The positive electrode materials obtained in the above embodiments and comparative examples were assembled into lithium-ion batteries with negative electrodes, electrolytes, and separators, wherein the negative electrode was a lithium sheet, the electrolyte used an equal mixture of ethylene carbonate and diethyl carbonate with 1 mol / L LiPF6 as an electrolyte, and the separator used a polyethylene porous membrane. Then, at 25°C and a voltage of 4.45V, the 0.1C capacity, 1C capacity, first efficiency, and 50-week cycle retention rate were tested. The test results are shown in Table 1:
[0121] Table 1
[0122]
[0123] From Table 1 we can see that:
[0124] The positive electrode material obtained by the present invention has excellent cycle performance, will not cause capacity reduction due to doping, and has a higher first effect; it can be seen from Example 1 and Examples 5-6 that the present invention preferably uses a gel-type cation exchange resin so that the cation exchange resin that adsorbs cations can effectively coat the positive electrode material, thereby effectively improving the electrical properties of the material; it can be seen from Example 1 and Examples 7-8 that during the coating process, the content of the cation exchange resin will also affect the coating effect; it can be seen from Example 1 and Example 9 that the gel-type cation exchange resin of the present invention requires wet coating, and the coating effect of dry mixing is reduced; it can be seen from Example 1 and Examples 10-11 that the present invention will dope the M-containing dopant doped in a single sintering process in steps, which can avoid the capacity reduction caused by doping and can also achieve surface gradient doping; it can be seen from Example 1 and Comparative Examples 1-3 that the combination of multiple sinterings of the present invention and the use of cation exchange resin for coating significantly improve the electrical properties of the material.
[0125] In summary, the present invention provides a positive electrode material and a preparation method and application thereof. The preparation method enhances the surface crystal structure stability of the material through multiple sintering and surface modification, binds metal cations to the surface of the positive electrode material, and obtains a uniformly coated positive electrode material after roasting, which effectively blocks the side reaction between the electrolyte and the positive electrode material, reduces the side reaction between the material surface and the electrolyte, greatly enhances the surface stability of the material, solves the problems of structural instability and poor interface stability of the material under high voltage, significantly improves the cycle performance of the material, and does not cause the capacity loss problem caused by multi-element doping, and can be used in high voltage systems above 4.4V.
[0126] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing a precursor and a lithium source and sintering them once to obtain a sintered product; (2) sintering the first sintered product in step (1) for a second time to obtain a second sintered product; (3) Mixing the cation exchange resin, the metal salt and the second sintered product of step (2), and then sintering for three times to obtain the positive electrode material.
2. The preparation method according to claim 1, characterized in that: The cation exchange resin in step (3) comprises a gel-type cation exchange resin; Preferably, the gel-type cation exchange resin comprises polymethyl methacrylate-ethylene glycol dimethacrylate copolymer.
3. The preparation method according to claim 1 or 2, characterized in that: A solvent is also added during the mixing process in step (3); Preferably, the mixing in step (3) comprises first mixing the cation exchange resin and the solvent, and then adding the metal salt and the di-sintered product in step (2) for mixing; Preferably, in the mixture obtained by mixing the cation exchange resin and the solvent, the content of the cation exchange resin is 0.05-0.2wt%; Preferably, in the mixture obtained by mixing in step (3), the concentration of the metal salt is 0.05-2.5 mol / L.
4. The preparation method according to any one of claims 1 to 3, characterized in that The metal salt in step (3) includes any one or a combination of aluminum salt and / or cobalt salt; Preferably, the temperature of the three sinterings in step (3) is 400-650°C, the time is 7-12h, and the heating rate is 2-8°C / min; Preferably, the three sintering steps in step (3) are performed in an air atmosphere; Preferably, after the mixing in step (3) and before the three sinterings, the solvent is first removed, and the method of removing the solvent includes drying and / or rotary evaporation, preferably rotary evaporation.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), before the secondary sintering, the first sintered product is mixed with an additive; Preferably, the additive includes a dopant containing M and / or a dopant containing P, wherein M includes any one of Al, Zr or Co or a combination of at least two thereof, and P includes any one of Sr, Y or Ti or a combination of at least two thereof; Preferably, in step (2), the mass ratio of the first sintered product to the dopant containing M is 1:(0.0001-0.1), and the mass ratio of the first sintered product to the dopant containing P is 1:(0.0001-0.1).
6. The preparation method according to any one of claims 1 to 5, characterized in that: The secondary sintering in step (2) is carried out at a temperature of 600-850°C, a time of 5-12h, and a heating rate of 2-8°C / min; Preferably, the atmosphere of the secondary sintering in step (2) is an air atmosphere; Preferably, after the secondary sintering in step (2), the sintered material is crushed to obtain a second sintered product, wherein the crushing method includes any one of jaw crushing, roller crushing, mechanical crushing or air flow crushing, or a combination of at least two of them.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (1), a first dopant and a second dopant are also added during the mixing process; Preferably, the mass ratio of the precursor to the first dopant is 1:(0.0001-0.1); Preferably, the mass ratio of the precursor to the second dopant is 1:(0.0001-0.1); Preferably, the first dopant is a dopant containing M, and the second dopant is a dopant containing N, wherein M includes any one of Al cations, Zr cations or Co cations or a combination of at least two thereof, and N includes any one of Mg cations, Ce cations, Sr cations, Y cations, W cations, Mo cations or Nb cations or a combination of at least two thereof; Preferably, the primary sintering temperature in step (1) is 800-980° C., the time is 6-17 h, the heating rate is 2-8° C. / min, and the atmosphere is an oxygen atmosphere; Preferably, the precursor in step (1) is Ni x Co y Mn z (OH)2, wherein 0.6≤x≤0.7, 0.05≤y≤0.2, 0.2≤z≤0.3, and x+y+z=1; Preferably, the particle size D50 of the precursor in step (1) is 3-5 μm, and BET is ≥ 8 μm. 2 / g.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing a precursor, a lithium source, a first dopant, and a second dopant, and then sintering them in an oxygen atmosphere at a temperature of 800-980° C. for 6-17 h at a heating rate of 2-8° C. / min, and then pulverizing to obtain a sintered product; Wherein, the mass ratio of the precursor to the first dopant is 1:(0.0001-0.1), and the mass ratio of the precursor to the second dopant is 1:(0.0001-0.1); (2) mixing the additive with the first sintered product of step (1), and then sintering the second sintered product at a temperature of 600-850° C. for 5-12 h in an air atmosphere at a heating rate of 2-8° C. / min, and then pulverizing the second sintered product. (3) mixing a cation exchange resin and a solvent to obtain a mixture having a cation exchange resin content of 0.05-0.2 wt %, adding a metal salt and the second calcined product of step (2) to the mixture to obtain a mixture having a metal salt concentration of 0.05-2.5 mol / L, drying and / or rotary evaporation to remove the solvent, and sintering the mixture three times at a temperature of 400-650° C. for 7-12 h at a heating rate of 2-8° C. / min in an air atmosphere to obtain the positive electrode material; Wherein, the cation exchange resin is a gel-type cation exchange resin.
9. A positive electrode material, characterized in that: The positive electrode material is prepared by the preparation method according to any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises the positive electrode material as claimed in claim 9.
Citation Information
Cited By
Preparation method of lithium cobalt oxide positive electrode material with O2 phase structure and lithium ion battery
CN122212266A
